Consensus and Conflict in G20 Global Economic Diplomacy - Abdurofiq, Atep; Putra, Gilang Rizki Aji; Yunus, Nur Rohim (ADALAH, 2024)
The G20 has emerged as the primary platform for global economic diplomacy, addressing matters about both developed and developing nations. Despite its goal of achieving consensus to foster inclusive and sustainable economic growth, the forum is frequently marked by discord and strain among its participants. This study examines the fluctuating patterns of agreement and disagreement in international economic negotiations within the G20. This article discusses the impact of the G20 in creating global economic policy by analyzing topics such as international trade, global finance, sustainable development, and poverty reduction. It also discusses the obstacles to establishing a consensus acceptable to all G20 members. This study offers a comprehensive analysis of the intricate dynamics inside the G20 conference and their potential impact on the future trajectory of the global economy.